Possible Repercussions of Opening Participation Banking Window of Conventional Banks Operating in Turkey - Unlu, Atilla; Yildiz, Kamuran (Hitit Univ, 2021)
With the establishment of the Islamic Development Bank in 1975, a strong foundation was laid for the existence of the participation banking sector in the world and the establishment process of participation banks in many countries began. The success of the development trend of participation banks and the possibility of reaching a size that will dominate the sector in the coming years caused many banks operating in the traditional banking sector to turn to this area. In this direction, traditional banks that want to get a share from the participation banking market have implemented alternative practices to enter the sector. The most widely used of these applications is the Islamic window opening model of a traditional bank. In this direction, there are 526 participation banks in the world as of 2020, and the fact that 219 banks within these banks serve within the participation banking window is a proof that the model is widely applied throughout the World. The lack of consensus among Islamic scholars on the implementation of the window system is seen as the most important problem in the adoption of the system. In this context, some Islamic scholars did not express a positive opinion on this issue, for reasons such as the establishment of a window system with the capital of traditional banks and their inability to contribute to the development of Islamic finance. Some Islamic scholars agreed that it would be more reasonable to receive services within the window system instead of working with a purely traditional bank. In addition, they did not see any inconvenience in the implementation of the said application due to the possibility of turning into a full-fledged participation bank by eliminating the interest-bearing structure of traditional banks included in the window system. The fact that Islamic scholars have basically two different views on the window system is reflected in Islamic financial markets. Accordingly, while in some countries there is no problem for traditional banks to become actors in Islamic finance markets through the window system, in some countries it is seen that these institutions cannot be included in Islamic finance markets. Saudi Arabia, Bahrain, Pakistan, United Arab Emirates, Indonesia and Ban-gladesh are the leading countries that actively use the window system among the countries with a large Muslim population. These countries (excluding Pakistan) are also among the top ten countries with the highest value for Islamic banking assets globally. Countries that are among the top ten countries with the highest value in terms of Islamic banking assets, but are not included in the window system or have abandoned the application; Iran, Kuwait, Qatar and and Turkey. Turkey's institutional acquaintance with Islamic finance culture dates back to 1985. Participation banks, which initially operated under the name of a private financial institution, took the title of bank as a result of the amend-ment made in the banking law in 2005.Although participation banks in Tur-key have a 36-year history, their market shares in both the national banking sector and international Islamic finance markets are relatively low. The in-ability of the participation banking sector to increase its market share in the Turkish banking sector is seen as a problem that needs to be solved for the participation banking sector and its stakeholders. In the face of this situation, while some actors in the sector tried to get rid of the problem by offering new products and services, the public authority announced that the participation banking window model could be put into use. (Medium Term Program (2019-2021) was published on September 20, 2018). In this direction, the main purpose of the study is; It presents an analysis of the potential impacts that could arise if traditional banks in Turkey were allowed to operate within the Islamic window system. When the literature on the window system is examined, it is seen that although there are many studies in the world, there is only one study on the application in Turkey. Within the scope of the research, the document review method, which is one of the qualitative research techniques, was used. As a result of the research, it was concluded that the possi-ble effects of the window application on the participation banking sector are multidimensional. In this direction, the strengths, weaknesses, opportunities and threats of the system were tried to be determined in order to analyze the possible effects.
Keywords: Finance; Islamic Finance; Traditional Banking; Participation Banking; Window Participation Banking